2012
DOI: 10.1111/j.1365-3156.2012.03096.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of acute pesticide poisoning in South Korea

Abstract: Abstractobjectives To investigate the magnitude and characteristics of the economic burden resulting from acute pesticide poisoning (APP) in South Korea.methods The total costs of APP from a societal perspective were estimated by summing the direct medical and non-medical costs together with the indirect costs. Direct medical costs for patients assigned a disease code of pesticide poisoning were extracted from the Korean National Health Insurance Reimbursement Data. Direct non-medical costs were estimated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…A study conducted in South Korea reports total economic cost of APP equivalent to US$ 150,000,000 which was 0.3% of the cost of total disease [38]. Though not modeled for under-reporting in this study, a recent Tanzanian study [18] reported that mortality from APP in Tanzania was 2.2 cases per 1,000,000.…”
Section: Discussionmentioning
confidence: 96%
“…A study conducted in South Korea reports total economic cost of APP equivalent to US$ 150,000,000 which was 0.3% of the cost of total disease [38]. Though not modeled for under-reporting in this study, a recent Tanzanian study [18] reported that mortality from APP in Tanzania was 2.2 cases per 1,000,000.…”
Section: Discussionmentioning
confidence: 96%
“…This difference could result from the existence of better surveillance systems in Sri Lanka and California compared to Tanzania. For example, the study by Pearson and colleagues, which demonstrated how close collaboration between stakeholders in Sri Lanka made use of surveillance data to implement effective policies to prevent pesticide poisoning, confirms the presence of a robust surveillance system for APP in that country [61]. Absence of information on the poisoning agent was associated with younger age in that adolescent girls were more likely to be involved in an APP where the agent was unknown (PRR Adolescent girls/ Adult women = 1.9, 95% CI =0.9-3.9).…”
Section: Discussionmentioning
confidence: 94%
“…Population-based APP incidence rates in this study (5.1/100,000) were far lower than reported in Nepalese females aged 15 to 50+ years (77.5/100,000) 47 and South Korean females aged 0 to 65+ years (27.4/100,000). 62 This could be explained by (a) poorer hygiene resulting in unsafe pesticide handling practices in Nepal or (b) under-reporting due to the lack of a surveillance system in Tanzania. For the Korean study, there were also age differences in the study population including children aged 1 to 10.…”
Section: Discussionmentioning
confidence: 99%